Green Synthesis of Gold Nanoparticles Using Clerodendrum trichotomum Thunberg for Antibacterial and Anticancer Applications - Shakoor A; Ferdous UT; Khan SA; Gulzar MM (International Journal of Nanomedicine)
Adnan Shakoor,1,2 Umme Tamanna Ferdous,2 Shakeel Ahmad Khan,3 Muhammad Majid Gulzar1,4 1Department of Control & Instrumentation Engineering, King Fahd University of Petroleum & Minerals, Dhahran, 31261, Saudi Arabia; 2Center for Bio Systems and Machines, King Fahd University of Petroleum & Minerals, Dhahran, 31261, Saudi Arabia; 3Department of Applied Biology and Chemical Technology, The Hong Kong Polytechnic University, Kowloon, 999077, Hong Kong; 4Interdisciplinary Research Center for Sustainable Energy Systems (IRC-SES), King Fahd University of Petroleum & Minerals, Dhahran, 31261, Saudi ArabiaCorrespondence: Shakeel Ahmad Khan, Department of Applied Biology and Chemical Technology, The Hong Kong Polytechnic University, Hung Hom, Kowloon, 999077, Hong Kong, Email shakilahmad56@gmail.comPurpose: The potential use of gold nanoparticles (AuNPs) in healthcare research has increased dramatically in recent years, owing to advancements in their synthesis techniques, including green synthesis. Although Clerodendrum trichotomum is a popular medicinal plant that harbors many bioactive phytochemicals in various parts of the world, the green synthesis of AuNPs using this precious plant is still under investigation. Therefore, this study aimed to explore the green synthesis of AuNPs from C. trichotomum Thunberg leaves (CTT-AuNPs) and their antibacterial and cytotoxic properties.Methods: AuNPs were synthesized from Clerodendrum trichotomum Thunberg and characterized using various microscopic and spectroscopic techniques. A serial dilution technique was used to determine the antibacterial activity of the synthesized CTT-AuNPs against two bacterial species, Klebsiella pneumoniae and Staphylococcus aureus. The cytotoxicity assay was carried out in the breast cancer cell line (MCF-7), whereas the biocompatibility test was performed in the kidney cell line (293T).Results: Multiple spectroscopic characterization techniques confirmed the successful synthesis of CTT-AuNPs. The average size of CTT-AuNPs was 19.1± 2.2 nm. The results of this study revealed that CTT-AuNPs showed strong antibacterial activity against S. aureus and K. pneumoniae, which was further confirmed using a live/dead dual staining assay. CTT-AuNPs also significantly reduced the proliferation of MCF-7 breast cancer cells to 32.67% at 120 μg/mL after 24 hours of incubation. These green-synthesized CTT-AuNPs exhibited excellent cytobiocompatibility with 293T kidney cells. The dual staining method further confirmed the cytotoxicity and biocompatibility of CTT-AuNPs compared with chemically synthesized AuNPs.Conclusion: This work will pave the way for the production of biocompatible AuNPs from C. trichotomum Thunberg that can be used in different disease treatments.Keywords: antibacterial, biocompatibility, Clerodendrum trichotomum Thunberg, cytotoxicity, gold nanoparticles